2005
DOI: 10.1111/j.1365-2257.2005.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic thrombocytopenic purpura in southern Turkey: a single-center experience of 29 cases

Abstract: In this retrospective, nonrandomized study, we describe our experience in the management of 29 consecutive patients with thrombotic thrombocytopenic purpura (TTP) treated with a combined therapy of plasma exchange (PE) and steroids at a single center. We compared the effectiveness of high-dose steroids (20-25 mg/kg methyl prednisolone) as first-line treatment in combination with PE therapy with the combination of standard-dose steroids (1 mg/kg methyl prednisolone) and PE in adult patients with TTP. Clinical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
4
14
0
Order By: Relevance
“…Espinosa et al (9) reported that 13% of patients with systemic TMA showed malignant hypertension. On the other hand, the frequency of intrarenal TMA with malignant hypertension has not been well described (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Espinosa et al (9) reported that 13% of patients with systemic TMA showed malignant hypertension. On the other hand, the frequency of intrarenal TMA with malignant hypertension has not been well described (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Adult TTP is considered to be an autoimmune disorder often accompanied by focal, reversible neurologic findings, and seizures [1,3]. Autoantibodies against ADAMTS13 work as inhibitors that induce a deficiency protease.…”
Section: Discussionmentioning
confidence: 99%
“…Immunomodulatory agents (eg, corticosteroids, vincristine, cyclophosphamide, azathioprine, cyclosporine, and high-dose immunoglobulins) have all been used to treat refractory TTP, all with unreliable effectiveness [1][2][3][5][6][7]. Efficacy of Rituximab for TTP patients by eliminating antibody-producing B lymphocytes has been reported in many previous literatures [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…41,42,44,[47][48][49][50][51] Plasma infusion should only serve as a temporizing measure until plasma exchange therapy can be delivered.…”
Section: Primary Ttp-husmentioning
confidence: 99%